Three dimension high definition manometry evaluated postoperative anal canal functions in children with congenital anorectal malformations - Zhao, Jiawei; Zhang, Yanan; Xiong, Yu; Du, Jingbin; Chen, Yongwei; Guo, Weihong; Huang, Jinshi (Frontiers in Pediatrics, 2023)
Background: We aimed to evaluate the function of the reconstructed anal canal in postoperative anorectal malformations (ARMs) patients through three dimension (3D) high-definition anorectal manometry. Methods: From January 2015 to December 2019, 3D manometry was performed as a postoperative functional assessment of patients with ARMs divided into age subgroups based on the time of manometry. Manometric parameters, such as the length of the anorectal high-pressure zone (HPZ-length), the mean resting and squeeze pressure of HPZ (HPZ-rest and HPZ-sqze), recto-anal inhibitory reflex (RAIR), and strength distribution of the anal canal, were collected and compared with age-matched controls. Their functional outcomes were analyzed with SPSS 23.0 software for statistical analysis. Results: 171 manometric measurements were performed on 142 postoperative patients (3 months~15 years). The HPZ-rest in all patients was significantly lower than in age-matched controls (p<0.05). HPZ-sqze was notably decreased in patients older than 4 years, whereas other age groups were comparable to controls (p<0.05). The proportions of asymmetric strength distribution and negative RAIR were higher in ARMs patients. The type of anorectal malformations and lower HPZ-rest were the impact factors affecting postoperative functional outcomes. Conclusions: The majority of the ARM patients had acceptable functional outcomes. 3D manometry can objectively assess the reconstructed anal canal function. The patients with fecal incontinence had a high proportion of extremely low HPZ-rest and HPZ-sqze, negative RAIR, and asymmetric strength distribution. The manometric details will help the clinicians explore the causes of defecation complications and guide further management.